1998
DOI: 10.1063/1.121535
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of the threshold fluence for extended defect formation in p-type silicon implanted with MeV Si ions

Abstract: Preamorphous damage in p-type Si implanted with MeV Si ions and annealed at elevated temperature is characterized using deep level transient spectroscopy (DLTS) and transmission electron microscopy (TEM). P-type Si was implanted with 4 MeV Si at doses from 1×1013 to 1×1014 cm−2 and annealed at 800 °C for 15 min. For doses below this critical dose, a sharp peak is observed in the DLTS spectrum, corresponding to the signature of point defects. Above the critical dose, a broad DLTS peak is obtained, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…For instance, after 1000 min at 370°C, about 65% of the initial VO centers in the FZ samples have been transformed into VOH 2 and the remaining fraction occurs as VO 2 pairs. Thus, the persistence of these vacancies cannot be neglected at temperatures above 400°C when such phenomena as thermal donor formation and generation of extended implantation-induced defects with DLTS signatures [66][67][68] …”
Section: ϫ3mentioning
confidence: 99%
“…For instance, after 1000 min at 370°C, about 65% of the initial VO centers in the FZ samples have been transformed into VOH 2 and the remaining fraction occurs as VO 2 pairs. Thus, the persistence of these vacancies cannot be neglected at temperatures above 400°C when such phenomena as thermal donor formation and generation of extended implantation-induced defects with DLTS signatures [66][67][68] …”
Section: ϫ3mentioning
confidence: 99%
“…Fatima et al 2,8 have determined the threshold doses corresponding to the transformation from point defects to extended defects in annealed samples. The threshold dose was shown to depend more strongly on the damage production than on the dose of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 Both electrical and structural characterization of Si, Ge, and Sn implanted samples consistently reveal that the formation of extended defects occurs at lower doses for heavier mass species. 8 In this study, we report details of the transmission electron microscopy ͑TEM͒ characterization of the extended defects formed in the various samples studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there have been several reports on electrically active defects observed in self-ion implanted Si after annealing at temperatures above 500°C. [1][2][3][4] Analyses of the deep level transient spectroscopy ͑DLTS͒ spectra revealed that most of the defect levels observed after post-implantation annealing at temperatures between 500 and 750°C are related to Si self-interstitial clusters. 1 For implant doses of у1ϫ10 13 cm Ϫ2 , the clusters appear to transform between electronic configurations and comparison of the thermal evolution behavior of these defect levels with transmission electron microscopy ͑TEM͒ analyses suggest that the small interstitial clusters are either the precusors of the ͕311͖ defects or that they compete with ͕311͖ defects as sinks for self-interstitials.…”
mentioning
confidence: 99%